Analyzing Determinants of Household Poverty in Brazil: An Empirical Study Using Ordinary Least Square Regression. - Javokhir Fakhriddinovich Boboyorov (Genius Journals, 2024)
Nowadays, household poverty is becoming one of the sharpest problems all around the world. To analyze the determinants of household poverty, significant family welfare factors were identified using Ordinary Least Square regression. Consumer expenditure was shown to be a credible welfare indicator for families and the first step in measuring poverty. In linear regression, the independent variable was logarithmically transformed. Brazil was investigated for the study. The study used 2000–2020 yearly time-series data. Household size was found to be a major factor affecting average household consumption. Education (especially literacy) and unemployment also reduce spending. Even with high independent variable significance, numerous additional factors can affect family poverty. Further research is needed to develop more effective home poverty programs
Keywords: Household Poverty; Ordinary Least Square Regression; Household Size